Pengaruh Communication Skill Dan Iklim Organisasi Terhadap Prestasi Kerja Dengan Kepuasan Kerja Sebagai Variabel Moderasi (Studi Pada Kelurahan se-Kota Bukittinggi) - Taufik Adi Putra (Jurnal Visi Manajemen, 2019)
This study aims to look at the effect of communication skills and organizational climate on work performance with job satisfaction as a moderating variable in all 24 Urban Village Offices in Bukittinggi City. The sample in this study was 94 civil servants consisting of 1 Village Secretary and 3 Section Heads in each Village Office in Bukittinggi City who were directly responsible to the Village headman. The data analysis method used is SEM (Structural Equation Modeling) analysis technique based on PLS (Partial Least Square) variance. Data collected through questionnaires, interviews, and documentation studies. The results of this study show that the variable communication skills and organizational climate both have a positive and significant effect on work performance variables in the Urban Village Offices in the City of Bukittinggi. So is the case with the variable job satisfaction which also has a positive and significant effect on the variable work performance. From the moderating variable used is the job satisfaction variable, it can be seen that job satisfaction strengthens the influence of communication skills on work performance, but conversely, the results obtained show that job satisfaction has a negative effect or weakens the relationship of organizational climate on employee job performance in Urban Village throughout Bukittinggi City.